A New Approach to Minimize Acellular Dermal Matrix Use in Prosthesis-based Breast Reconstruction. Issue 7 (July 2015) - Hadad, Ivan; Liu, Allen S.; Guo, Lifei
Abstract : Background: Acellular dermal matrices (ADMs) are often used to improve lower-pole contour, as well as allow for single-stage reconstruction, but numerous studies have shown an increased complication rate using ADM. As such, our group has developed a minimal-ADM-use technique to lower complications while effectively recreating lower-pole contour. Methods: A total of 380 postmastectomy prosthesis-based breast reconstructions were performed in 265 patients by a single surgeon. One hundred eight reconstructions were performed using the traditional ADM technique, with a large piece of ADM along the entire inferior and lateral borders. Two hundred twenty-five reconstructions were performed with the minimal-use technique, patching only the lateral area of the reconstruction. Thirty-five reconstructions were performed without the use of any ADM for high-risk reconstructions, most often in morbidly obese patients. Results: Comparing the traditional technique with the minimal-use technique, the seroma rate dropped from 3% to 0%. The rate of infection and reconstruction loss fell from 9% to 1%. Upon greatly reducing or eliminating the use of ADM use in obese patients, the seroma rate decreased from 15.4% to 5.7%, and the reconstruction loss rate decreased from 38% to 9%. Conclusions: This article describes a new surgical approach to minimize the amount of ADM necessary to create an aesthetically pleasing breast reconstruction. We believe that this approach helps avoid the complications of seroma, infection, and loss of the reconstruction. In certain obese patients, total avoidance of ADM may be the better choice.